If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-12x+6)=(4x-12
We move all terms to the left:
(-12x+6)-((4x-12)=0
We get rid of parentheses
-12x-((4x-12)+6=0
| 15x-31=9x+11=180 | | 6x+2=x+3=9 | | 18-2x+6=26- | | 0.4x+10=3/5x+12 | | 15=6+d;d=3 | | -264=-10p+4(9-5p) | | 26=r-10 | | 20-4r/5r=10 | | -4p+8=16 | | 7=d+103 | | -9(1-8v)=207 | | y-44=19 | | 4z/3z=9 | | 7y=+6+2y+6= | | 22=10(2)^(2x)-8 | | 15=6+d; | | 4k−2=18 | | 6t-2/4+4(t+1)(t=5) | | -10+10(7n+5)=-170 | | 5b+2(-1-7b)=10+3b | | f+–371=–627 | | 40-9yy=2 | | 5/4=d/48 | | -3+10(1+9n)=727 | | 3.75+1.625x=86 | | 3c-5c=0 | | 13x-2+3x-4=5x-7 | | 49=h-5 | | p+47=73 | | 12z=72. | | 253=114-v | | s-48=28 |